An Overview of Personal Hygiene Behavior in Pregnant Women with Anemia in the Work Area of Puskesmas Blado II - Kurniasaputri, Sekar Meiningtyas; Nurlaela, Emi (Prosiding University Research Colloquium, 2023)
In Indonesia, the prevalence of anaemia in pregnant women is still high, although the government has taken precautions by providing blood (Fe) supplements, the anaemia rate remains high. Pregnant women who are at high risk of parasitic infections if they do not maintain personal hygiene have been proven to directly contribute to anaemia. this study aims to describe an overview of personal hygiene behaviour in pregnant women with anaemia. samples taken were 36 pregnant women with anaemia in the work area of Puskesmas Blado II with sampling total technique. it is a descriptive quantitative and questionnaires about hygiene personal behaviour in pregnant women and checking haemoglobin using the Quick-Check tool. it stated pregnant women with light anaemia were 33 (91.7%) while good personal hygiene behaviour in pregnant women was 19 (52.8%). there is more than half of the personal hygiene of pregnant women with anaemia so it needs to be maintained and increased.